Effectiveness Of Surgical Treatment of Appendicitis in Young Children Using Laparoscopy - Itueva, Bika Dzhalalutdinovna; Salamov, Isabek Islamovich; Khasieva, Rayana Ismailovna; Andreevna Sotnik, Elizaveta; Agarzaeva, Sabiyat Nezhmudinovna; Dzhanaralieva, Ayna Khamidovna; Dzhanaralieva, Aminat Khamidovna (Journal of Neonatal Surgery, 2025)
Annotation. In the scientific community there is a growing interest in minimally invasive methods of surgical intervention, in particular in laparoscopic appendectomy in young children. The aim of this study was to evaluate the efficacy and safety of the laparoscopic approach in the treatment of acute appendicitis in patients aged 3 to 7 years compared to traditional open appendectomy. The analysis of clinical and epidemiological data, peculiarities of surgical intervention and postoperative period was carried out. The results of the study revealed a decrease in the incidence of wound complications and a reduction in the duration of hospitalisation in children operated laparoscopically. At the same time, the indices of operation time and conversion to open surgery remained at an acceptable level. The study concludes that the laparoscopic method is highly effective in terms of reducing traumatic injuries, improving quality of life indicators and favourable economic effect..